Improving the Historical Knowledge and Writing of Students With or At Risk for LD. (November 2017) - De La Paz, Susan; Wissinger, Daniel R.
In this study, we explored the potential of two forms of discussion (disciplinary vs. traditional) for 39 sixth- and seventh-grade students with or at risk for learning disabilities (LD), before writing historical arguments. Nine teachers who led small group discussions in six heterogeneous social studies classrooms implemented the intervention. Students who were involved in disciplinary discussions ( n = 19) scored statistically higher than their peers who engaged in traditional discussions ( n = 20) on a measure of historical knowledge (partial η 2 = .23); they also wrote essays with better persuasive quality (partial η 2 = .43) and greater evidence of historical thinking (partial η 2 = .40). A delayed posttest delivered 8 weeks after instruction ended revealed that students in the experimental condition continued to write in more historically sophisticated ways than did students in the comparison condition (partial η 2 = .19). Challenges, however, remain for struggling learners who must now meet basic and advanced disciplinary literacy goals.